Role of Motorcycle Running Lights in Reducing Motorcycle Crashes during Daytime; A Review of the Current Literature - Seyed Rasoul Davoodi; Seyed Mohamad Hossayni (Bulletin of Emergency and Trauma, 2015)
In comparison to other transportation modes, riding motorcycle is prone to accidents. Motorcyclists are more exposed to physical injury than the car drivers. Many multi-vehicle motorcycles crashes occur, there is right-of- way violation takes place in which another vehicle turns in fronts of a motorcycle, or a sudden cross of path of an on-coming motorcycle. One main factor which leads to high rate of motorcycle crashes is lack of conspicuity of motorcycles by other road users especially during day time traffic. This paper highlights previous studies on the implementation of motorcycle DRLs, focusing on the efficacy of the DRLs to improve motorcycle conspicuity. This paper reviews the impacts of DRL by motorcyclists on multi-vehicle motorcycle crash. The three categories of effects of motorcycle DRLs were reviewed. All literature, supporting that operating headlights during daytime appears to be an influential and effective approach to reduce rate of collision by improving motorcycle’s conspicuity in traffic. The motorcycle DRLs managed to reduce about 4 to 20% of motorcycle crash risk. This paper also recommends that motorcycle DRLs must be used globally, especially in countries with high motorcycle accidents to improve the safety of the riders as well as their pillion riders.